Subjective Well-Being as a Determinant of Consumer Innovativeness in Seniors - Tomasz OLEJNICZAK; Magdalena OLEJNICZAK (Communications of International Proceedings, 2020)
The aging of the population is a long-term trend that began in Europe several decades ago. This trend is visible in the transformation of the age structure of the population and is reflected in the growing share of elderly people in the general population, combined with the corresponding decreasing share of the working-age population. As people age, they undergo general changes in their bodies in the physical, physiological, and mental spheres, which changes their market behavior. The importance of recognizing the attitudes of older people in the process of purchasing products results primarily from the fact that Poland is the fastest aging country in the European Union. Older people are perceived stereotypically as being closed to new things, with strongly shaped traditional attitudes. However, research results show that the senior segment is highly diverse. Increasingly, older consumers show interest in new products and services. The research aimed to determine the impact of subjective well-being on consumer innovativeness. This study was conducted in Poland in 2018 on a sample of 1,617 people. The respondents were selected using the quota selection method; the structure of the sample examined according to the criterion of gender and age was the same as the structure of the elderly population in the Wielkopolska region. The presented research results they indicate, that seniors are not a homogeneous group. At the analyses carried out indicate that the most important determinants of the process of acceptance of product innovations by seniors include, first of all, individual (subjective) variables. The inclusion of subjective well-being consisting of specific individual components in the analyses completed the picture of the shaping of attitudes of seniors towards new products. Older consumers may be an attractive segment for innovative companies.
Keywords: Consumer Behavior; Product Innovation; Older Consumers; Consumer Innovativeness; Subjective Well-Being; Seniors.